DEVELOPMENT OF MANAGEMENT OF REPRODUCTION OF FIXED ASSETS - V. Bobylev; N. Starostina; E. Starostina (Вестник университета)
The article is devoted to topical issues of development of management of reproduction of fixed assets. The authors emphasize an important role for the successful solution of important problems of development management of such forms of reproduction of fixed assets as the repair, reconstruction, modernization or upgrading in terms of implementation of innovation investment in the modern requirements of the domestic market economy.